Polymorphism in the promoter region of von Willebrand factor gene and von Willebrand disease type 1 - Simon, Daniel (2003)
The -1185A/G polymorphism in the 5’-regulatory region of the von Willebrand factor (VWF) gene was associated with VWF plasma levels in a normal population. This study was undertaken to evaluate whether there is a relationship between this polymorphism and type 1 von Willebrand disease (VWD), a disorder characterized by a quantitative deficiency of VWF. The association between this polymorphism and plasma VWF levels in normal Brazilian individuals was also analyzed. Control subjects (n = 460) and type 1 VWD patients (n = 41) were studied. Polymerase chain reaction (PCR) amplification of the 864-bp VWF promoter region followed by AccII restriction-digestion was used to identify the -1185A/G genotypes. The -1185G allele frequency was 57% in normal individuals and 63% in type 1 VWD patients, this difference was not significant (p = 0.29). No significant association was observed between -1185A/G genotypes and VWF plasma levels in normal individuals, although VWF levels were in the same direction as those reported by another study, with subjects carrying the G allele having the lower levels. These results suggest that -1185A/G polymorphism is not associated with the partial deficiency of VWF in type 1 VWD patients.